Mobilisasi Penjaga Suar dan Penentuan Rute Kapal Distrik Navigasi Kelas I Surabaya Dengan Simulasi Diskrit - Hakim, Abdul -; Dwi Putranta, A.A Bagus Dinariyana (Matrik : Jurnal Manajemen dan Teknik Industri Produksi, 2024)
ABSTRACT The route selection in a ship operation is important thing, a ship is expected to operate safely, effectively and efficiently. Tanjung Perak Marine Navigation Service ship beside carried out task to maintenance buoy and other navigation aid also have a task to mobilization of lighthouse keeper in their work area. The ideal condition according to the provisions of the Directorate of Navigation is that every ship must sail at least 118 days per year. However, due to the limited fuel oil budget, these ideal conditions could not be achieved, where the pattern of routes I and II carried out by Class I ships in the form of logistics delivery and roster schedule of lighthouse keeper, which were originally 4 times per year, only became 2 times per year. Whereas class II ships only carry out maintenance on route III and IV. For the V route pattern, namely Lebaran, Christmas and New Year, transportation currently only carried out by class I ships, however class II ships in this study are simulated to also be able to serve route V taking into account the availability of passenger capacity and fulfillment of ship sailing time. This research was conducted to analyze several existing route options, in order to obtain a route that can be used as a reference in terms of ship operations that meet existing limitations such as the need for fuel, fresh water and in accordance with the roster schedule for each lighthouse keeper. Several other things are taken into consideration in selecting routes and officer schedules including the weather factor, the amount of cargo to be transported and unloaded, as well as the type of maintenance work that is in an Navigation Aid (SBNP) Due to these dynamic condition, the research method used in this study is Discrete event simulation. The simulation begins with modelling 5 (five) existing route with 4 (four) navigation ship. Simulation is carried out based on type of ship, route scenario, location of lighthouse and assignment schedule of lighthouse keeper, as well as existing limitation. The expected result are determination of the route and type of ship that can meet personel assignment schedule, fuel budget availability and minimum sailing time per year. Keyword: sesuaikan dengan kata kunci bahasa Indonesianya